Radicality of lymphadenectomy in lung cancer resections by thoracotomy and video-assisted thoracoscopic approach: A prospective, multicentre and propensity-score adjusted study. (March 2022) - Obiols, Carme; Call, Sergi; Rami-Porta, Ramón; Jaén, Ángeles; Gómez de Antonio, David; Crowley Carrasco, Silvana; Royo-Crespo, Íñigo; Embún, Raúl
Highlights: The intensity of the lymphadenectomy performed by VATS tends to be worse in comparison with the open approach. A higher percentage of systematic nodal dissection, pN1 and pN2 disease was found in the open approach. Abstract: Objective: To analyse differences in intraoperative nodal assessment in patients undergoing lung cancer resection by thoracotomy and video-assisted thoracoscopy (VATS) in the Spanish Video-Assisted Thoracic Surgery Group (GEVATS). Methods: Prospective multicentre cohort study of anatomic pulmonary resections (n = 3533) performed from December 2016 to March 2018. Main surgical, clinical and oncological variables related with lymphadenectomy were compared according to surgical approach. Corresponding tests for homogeneity were performed. Multiple logistic regression analyses were used to determine the odds ratio (OR) and 95% confidence interval (95%CI). Covariate adjustment using the propensity score (PS) was performed to reduce confounding effects. Results: After exclusions, 2532 patients were analysed. Systematic nodal dissection (SND) was performed in 65%, with a median of resected/sampled lymph nodes (LN) of 7 (IQR 4–12) and pathologic (p) N2 and uncertain (u) pNu rates of 9.4% and 28.9%, respectively. At multivariate analysis, the following were associated with thoracotomy (OR; 95%CI): SND (1.4; 1.08–1.96; p = 0.014), staging mediastinoscopy (2.6; 1.59–4.25; p < 0.001), tumor > 3 cm (2.1; 1.66–2.78; p < 0.001), central tumor (2.5; 1.90–3.24; p < 0.001); pN1 (1.8; 1.25–2.67; p < 0.002), pN2 (1.8; 1.18–2.76; p = 0.006), lower FEV1 (0.9; 0.98–0.99; p < 0.001), squamous cell carcinoma (1.5; 1.16–1.98; p = 0.002) and inexperienced surgeons in VATS (compared with > 100 VATS experience) (37.6; 13.55–104.6; p < 0.001). After PS adjustment, SND maintained the OR, but in the limit of signification (1.4; 1–1.98; p = 0.05). Nodal upstaging was significantly higher in the thoracotomy group. Complication rates of SND and no SND were similar. Conclusions: Thoracotomy was associated with a more thorough lymphadenectomy in GEVATS. Therefore, intraoperative lymph node evaluation performed at VATS should be improved to have better prognostic information and more solid grounds to indicate adjuvant therapy.